Penetrating Keratoplasty Using the Femtosecond Laser: A Comparison of Postoperative Visual Acuity and Astigmatism by Suture Pattern. Issue 12 (December 2018) - Shumway, Caleb L.; Aggarwal, Sahil; Farid, Marjan; Muniz-Castro, Hannah; Jarstad, Allison; Garg, Sumit; Kedhar, Sanjay; Wade, Matthew
Abstract : Purpose: To compare the effect of 3 common suturing techniques on eyes that received femtosecond laser-enabled penetrating keratoplasty (FLEK) with a zig-zag configuration at the Gavin Herbert Eye Institute, University of California- Irvine, California. Methods: This is a retrospective chart review of a series of 319 eyes of 286 patients who underwent FLEK with a zig-zag configuration. One hundred fifty-seven eyes had running sutures, 136 eyes had simple interrupted sutures, and 26 eyes had combined sutures (single running and simple interrupted). The main outcome measures were uncorrected distance visual acuity, best spectacle-corrected visual acuity (BSCVA), and topographic astigmatism (TCyl). These parameters were recorded for the first year of follow-up regardless of suture removal status and also after full suture removal. Results: At 3 months, the BSCVA of the running, interrupted, and combined suture groups was 0.22 (±0.2), 0.41 (±0.3), and 0.29 (±0.1), respectively ( P < 0.01). The mean TCyl of the running, interrupted, and combined groups at 3 months was 3.95 (±2.7), 6.41 (±4.4), and 5.44 (±3.3) D, respectively ( P < 0.01) All sutures were removed in 190 of 319 eyes, and at the last recorded visit, the mean BSCVA was 0.18 (±0.2), 0.34 (±0.2), and 0.19 (±0.2) logarithm of the minimum angle of resolution in the running, interrupted, and combined groups, respectively ( P < 0.01) and mean TCyl was 4.51 (±2.8), 5.62 (±3.7), and 4.57 (±2.9) D, respectively ( P = 0.11). Conclusions: Better visual acuity after full suture removal was observed in the running suture group; however, the subgroups of patients with keratoconus were similar after all sutures were removed.